Direction Transmission Protocol of the Highway Traffic Information Assisted by Roadside-Infrastructure - Jianghong Han; Fan Yang; Zhengyu Liu; Lei Shi; Li Zhang (Dianxin kexue)
Existing VANET network broadcast transmission protocols have low channel utilization, and easily lead to channel congestion and other issues, so improved protocol assisted by roadside- infrastructure was proposed. It used roadside-infrastructure to cluster the vehicle. In the clustering, every sending data frame added the vehicle number to its head and each vehicle node received and transmitted the packets selectively. The results show that the improved protocol is able to improve the transmission channel usage effectively, and the effective information transfer rate is able to be increased by 20%.